2011
DOI: 10.1111/j.1442-9071.2011.02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of c-Myc in pterygium and cultured pterygial cells

Abstract: c-Myc expression is reduced in pterygium compared with normal conjunctiva. Transforming growth factor beta1 can elevate the downregulated c-Myc in cultured pterygial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Interferon-gamma response belongs to immune responses which have been associated with pterygium ( 58 ). MYC, as a proto-oncogene is also involved in the disease ( 59 ). The result of Wnt beta-catenin signaling is consistent with our previous GO analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon-gamma response belongs to immune responses which have been associated with pterygium ( 58 ). MYC, as a proto-oncogene is also involved in the disease ( 59 ). The result of Wnt beta-catenin signaling is consistent with our previous GO analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signal pathway, which is activated in nearly all cancers, has been shown to also be activated in pterygium tissue. [30][31][32] Loss of heterozygosity (LOH) and microsatellite instability (MI) are characteristics of transformed cells. [33][34][35] Detorakis et al 33 have found that LOH is common with pterygia most often at 9p (48%), followed by 17q (42%), but MI of DNA was uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…The ETC (Electronic Toll Collection) is designed to solve the traffic congestion problems and to improve the passage efficiency at the toll station. Some highways have set up the ETC lanes [1] in recent years, most of which are converted from the existing MTC lanes, and the traffic volume is significantly higher than ETC [2]. The toll station with ETC and MTC is called hybrid highway toll station.…”
Section: Introductionmentioning
confidence: 99%